Toxicity Test of Ethanol Extract Ant Plant Local Aceh (Mymercodia sp) Method of BSLTLarvae Shrimp Artemia salina Leach - Frengki F; Roslizawaty R; Desi Pertiwi (Jurnal Medika Veterinaria, 2014)
Toxicity test and phytochemical screening of ant plant ethanol extract were done. The toxicity test was done by employing the Brine Shrimp Lethality Test (BSLT) method. Sample of ant plant taken from the Aceh Besar forest have been extracted with ethanol. The sample was thenconcentrated using a rotary evaporator until a crude extract was obtained. The extract was tested by toxicity to larva Artemia salina L. Thetoxicity test for larvae Artemia salina Leach have been done by employing the Brine Shrimp Lethality Test (BSLT) method at four concentrationlevels, i.e: 250 ppm, 125 ppm, 50 ppm, and 25 ppm. The result of the research showed that ethanol extract of ant plant Aceh had acute toxicityby LC value 61.11 ppm. The extract had identified were fenolik, saponin, steroid and terpenoid.____________________________________________________________________________________________________________________Key words: rine Shrimp Lethality Test, LC5050, Ant Plant, Aceh, Bphytochemical Screening